Pollution Physique Et Bactériologique De L’eau Du Fleuve Dans La Basse Vallée De L’ouémé Pendant Les Périodes De Basses Et Hautes Eaux Au Bénin - Adjagodo A.; Agassounon Djikpo Tchibozo M.; Kelomè N.C.; Vissin E.W.; Agbossou E. (European Scientific Journal, ESJ, 2017)
The objective of this study is to assess the water river quality of the Lower Valley of Ouémé in Benin. Two river water sampling campaigns were carried out during low and high water. At each sampling campaign, eleven (11) sampling sites were selected and at each site four samples were taken, making a total of 44 water samples. Hydrogen potential, dissolved oxygen, suspended matter and turbidity were measured in situ. Fecal contamination germs such as total coliforms, thermotolerant coliforms, Escherichia coli and fecal enterococci were counted by the membrane filtration technique. The results of the physical analyzes reveal that the pH measured in the water samples conformed to the WHO standard except turbidity. The results of the bacteriological analyzes in 100 mL of water sample of the river reveal average bacterial loads in periods of low and high waters which vary respectively from 2.57.10 2 ± 451 CFU and 3.35.102 ± 459 CFU for total coliforms; 1.42.102 ± 315 CFU and 1.55.102 ± 251 for thermotolerant coliforms; 0,79.102 ± 216 CFU and 1.55.102 ± 251 for E. coli. The Enterococci are absent in the waters during these two periods. The high burden of these germs counted in the high water period may be due runoff phenomenon and unhygienic behavior observable in the study area.